Techno-economic analysis of protein concentrates production from brewer’s spent grains - Yilin Li; Ruoshi Xiao; Zach McCaffrey; Ronald Haff; Nasib Qureshi; Yixiang Xu; Haibo Huang (Bioresource Technology, 2026)

A composite ecological drought index integrating multi-source water and heat stress with time-lag effects: Insights from the Yellow River Basin - Jingtian Ma; Lianqing Xue; Yuanhong Liu; Saihua Liu; Ruoshi Xu (Journal of Environmental Management, 2026)

Long-term water quality monitoring and assessment in lakes along large-scale water diversion project: An ensemble machine-learning approach using Graph Convolutional Network and Random Forest - Ruoshi Xu; Lianqing Xue; Yuanhong Liu; Saihua Liu; Jingtian Ma; Wujie Zhou (Journal of Water Process Engineering, 2026)

Indian summer monsoon and winter Total Solar Irradiance signals in the tree‐ring δ 18 O from foothills of High Asia, northern Pakistan - Qiang Li; Yu Liu; Ashish Sinha; Gayatri Kathayat; Xiangyu Duan; Ruoshi Liu; Chenxi Xu; Huiming Song; Congxi Fang; Muhammad Faheem Siddiqui; Hai Cheng (International Journal of Climatology, 2023)
A tree‐ring stable oxygen isotope (δ 18 O) chronology was developed for the past 171 years by four Abies pindrow trees growing in southwest foothills of High Asia, northern Pakistan, which is correlated with observed and modelled δ 18 O of precipitation in Islamabad over the instrumental period. The averaged tree‐ring δ 18 O chronology is significantly negative correlated with local ( r = −.651, p n = 38) and regional ( r = −.664, p n = 65) summer precipitation variations. Analysis of vertically integrated water vapour flux and surface wind field suggests that the sampling site is located at the northern limit of the Indian summer monsoon (ISM). Our tree‐ring δ 18 O series is significantly ( p n = 143) negatively correlated with observed Homogenous India rainfall, All Indian rainfall, Core‐Monsoon India rainfall and Northwest India rainfall. This is the first detected ISM signal from tree‐ring δ 18 O over northern Pakistan. Several ISM‐related paleoclimate proxies, including three stalagmites δ 18 O series (Sahiya cave, Jhumar cave and Qunf cave) and a tree‐ring δ 18 O series (Manali), show consistent variability and a correlation coefficient of .566 ( p n = 165) with our tree‐ring δ 18 O, suggesting that a combination of multiple proxies may be potentially useful to understand the full perspective of ISM before instrumental era. In addition, we found that the satellite‐observed winter Total Solar Irradiance exerts influence on the tree‐ring δ 18 O variation ( r = .643, p n = 38), which may be linked to runoff of the Indus River and ISM precipitation.

Seismic resilience of extra-large LNG tank built on liquefiable soil deposit capturing soil-pile-structure interaction - Noor Sharari; Behzad Fatahi; Aslan Hokmabadi; Ruoshi Xu (Bulletin of Earthquake Engineering, 2022)
Assessment of seismic resilience of critical infrastructure such as liquefied natural gas (LNG) storage tanks, is essential to ensure availability and security of services during and after occurrence of large earthquakes. In many projects, it is preferred to build energy storage facilities in coastal areas for the ease of sea transportation, where weak soils such as soft clay and loose sand with liquefaction potential may be present. In this study, three-dimensional finite element model is implemented to examine the seismic response of a 160,000 m 3 full containment LNG tank supported by 289 reinforced concrete piles constructed on liquefiable soil overlaying the soft clay deposit. The seismic soil-structure interaction analysis was conducted through direct method in the time domain subjected to the 1999 Chi-Chi and the 1968 Hachinohe earthquakes, scaled to Safe Shutdown Earthquake hazard level for design of LNG tanks. The analyses considered different thicknesses of the liquified soil deposit varying from zero (no liquefaction) to 15 m measured from the ground surface. The key design parameters inspected for the LNG tank include the acceleration profile for both inner and outer tanks, the axial, hoop and shear forces as well as the von Mises stresses in the inner tank wall containing the LNG, in addition to the pile response in terms of lateral displacements, shear forces and bending moments. The results show that the seismic forces generated in the superstructure decreased with increasing the liquefied soil depth. In particular, the von Mises stresses in the inner steel tank exceeded the yield stress for non-liquefied soil deposit, and the elastic–plastic buckling was initiated in the upper section of the tank where plastic deformations were detected as a result of excessive von Mises stresses. However, when soil liquefaction occurred, although von Mises stresses in the inner tank shell remained below the yield limit, localised stress concentrations were observed in the lower section of the tank near the base, increasing the risk of the elephant foot buckling. The lateral displacements, shear forces and bending moments in the piles increased with increasing depth of the liquefied soil. Indeed, increasing the pile lateral displacement amplified the bending moment at the pile head, thus resulting in increases in the pile bending moments especially when the liquefied soil depth exceeded one third of the entire soil deposit. In particular, the bending moment at the pile head exceeded the yield moment capacity of the pile and subsequent plastic hinges were formed. Moreover, when the thickness of the liquefied soil was more than half of the entire soil depth, the mobilised bending moments in the piles exceed the ultimate moment capacity of the pile and thus total failure of the piles were observed. In addition, in the absence of liquefied soil layer, the inertial interaction had a dominant impact on the pile response in this study. However, with increasing the thickness of the liquefied layer, further loads were developed in the piles due to amplified kinematic interaction, while the inertial interaction-induced loads decreased.

Mechanism of Cr(VI) reduction by Lysinibacillus sp. HST-98, a newly isolated Cr (VI)-reducing strain - Jia Chen; Xiaoguang Li; Longzhan Gan; Guangyang Jiang; Ruoshi Zhang; Zhe Xu; Yongqiang Tian (Environmental Science and Pollution Research, 2021)

Application of exogenous substances reduces tobacco-specific nitrosamines content by regulating biosynthesis of nicotine and nitrite in burley tobacco - Siwei Liang; Jinpeng Yang; Jun Zhou; Jun Yu; Yanjun Ma; Ruoshi Bai; Fangsen Xu; Chunlei Yang (Acta Physiologiae Plantarum, 2013)